2017
DOI: 10.1039/c7ew00171a
|View full text |Cite
|
Sign up to set email alerts
|

Solids retention time, influent antibiotic concentrations, and temperature as selective pressures for antibiotic resistance in activated sludge systems

Abstract: This paper evaluates changes in antibiotic resistance during biological wastewater treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Some studies have shown that longer SRTs may be effective for the attenuation of a small number of antibiotics (Gerrity et al., ; Salveson et al., ). However, other studies have shown that longer SRTs are generally ineffective for antibiotic attenuation and may even lead to increased prevalence of antibiotic resistance (Neyestani, Dickenson, McLain, Obergh et al., ; Neyestani, Dickenson, McLain, Robleto et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that longer SRTs may be effective for the attenuation of a small number of antibiotics (Gerrity et al., ; Salveson et al., ). However, other studies have shown that longer SRTs are generally ineffective for antibiotic attenuation and may even lead to increased prevalence of antibiotic resistance (Neyestani, Dickenson, McLain, Obergh et al., ; Neyestani, Dickenson, McLain, Robleto et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, discharges of hospital wastewater, which may contain antibiotic concentrations at the high μg/L level (Brown, Kulis, Thomson, Chapman, & Mawhinney, ), may periodically cause antibiotic spikes in the raw wastewater entering a municipal water resource recovery facility. These higher influent antibiotic concentrations may lead to increased prevalence of antibiotic resistance (Neyestani, Dickenson, McLain, Obergh et al., ), but as long as the concentrations remain subclinical, they may not have a significant impact on microbial community function (Li & Zhang, ; Neyestani, Dickenson, McLain, Obergh et al., ). The potential impacts on overall microbial community structure are less clear, although there is evidence to suggest that exposure to hospital wastewater can select for unique microbial taxa (Ahn & Choi, ).…”
Section: Introductionmentioning
confidence: 99%
“…() found that removals of trace organics such as ibuprofen (almost 100%) and several other antioxidants (the variety between 43% and 99%) increased at higher SRTs. In laboratory‐scale research, the proliferation of antibiotic resistance genes and antibiotic‐resistant bacteria had decreased and sometimes increased at higher SRT (Neyestani, Dickenson, McLain, Obergh, et al., ). Neyestani et al found that the prevalence of ARB in the activated sludge process increased at higher SRTs (2,7, and 20 days) and was more pronounced at higher temperatures.…”
Section: Args In Biological Treatmentmentioning
confidence: 68%
“…Fortunately, many previous studies have reported that some current treatment plant designs may remove ARGs and ARB, at least partially, and different processes have their own characteristics for different types of ARGs. For example, studies have found that solids retention time may be an important factor to the treatment removal efficiency of ARGs in activated sludge processes (De Sotto et al., ; Neyestani, Dickenson, McLain, Obergh, et al., ; Neyestani, Dickenson, McLain, Robleto, et al., ). Characteristics of different treatment processes are discussed below in detail.…”
Section: Antibiotic Resistance Genes In Water Resource Recovery Facilmentioning
confidence: 99%
“…The results of the Water Environment Research, Volume 90, Number 10 -Copyright © 2018 Water Environment Federation study suggested that up to 40% increase in the prevalence of resistant bacteria was observed in the activated sludge samples collected from the reactors with the longer SRTs.The authors suggested that longer SRT may have positively selected ARBs and/or resulted in false positive results due to higher concentrations of thymine, thymidine, or other extracellular constituents. In a different study by the same group, potential of proliferation of AMR during biological wastewater treatment was investigated(Neyestani, Dickenson, McLain, Obergh, et al, 2017). An SRT of 1, 7 and 20 days was evaluated using ambient concentrations of antibiotics while an SRT of 7 days was evaluated using concentrations of 1x, 10x and 100x of ambient concentration using lab-scale activated sludge reactors.…”
mentioning
confidence: 99%